Synthesis of sterically encumbered di- and triarylamines by palladium-catalysed C–N coupling reactions under mild reaction conditions. Issue 11 (1st March 2022) - Neigenfind, Philipp; Knyszek, Daniel; Handelmann, Jens; Gessner, Viktoria H.
Abstract : A simple Pd-catalyzed C–N coupling protocol for the formation of diarylamines as well as bulky triarylamines under mild reaction conditions has been developed based using a single ylide-substituted phosphine ligand. Abstract : The synthesis of bulky, ortho -substituted triarylamines often represents a synthetic challenge, but is highly desirable due to the use of these compounds in organic electronics. Here, we report on a systematic study of the application of ylide-substituted phosphines (YPhos) in the Pd-catalysed formation of bulky di- and triarylamines. Screening of different ligands showed that whereas diarylation is possible with most of the YPhos ligands tested, triarylamines are most efficiently formed with the smallest, most flexible YPhos ligand, keYPhos, featuring a methyl group in the ligand backbone. This ligand allowed the synthesis of a series of sterically encumbered di- and triarlyamines in good to high yields at low temperatures of only 60 °C. The optimized protocol enabled the incorporation of up to three ortho -substituents for the triarlyamines, thus representing a convenient and mild method for their synthesis. This was demonstrated by means of the synthesis of structures used as organic electronic materials.